1956
DOI: 10.1139/b56-052
|View full text |Cite
|
Sign up to set email alerts
|

Selection Techniques in Screening for Coumarin-Deficient Sweet Clover Plants

Abstract: The loss of coumarin from sweet clover leaf samples amounted to 70 to 75% when the samples were air-dried for 10 days and 21 to 51% when oven-dried at 175° F. for one hour. Fresh leaf material placed in 2.5 N NaOH and stored in darkness at room temperature showed no loss of coumarin over a six month period but when stored in light at room temperature losses were evident: in 10 days and very heavy after six months' storage. Coumarin content was maximum in flower buds and fresh leaves from the tip of branches. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1958
1958
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the past, workers have carried out analyses on fresh plant material, or on material dried either in a current of air at room temperature or by heating al: temperatures varying from 60-100°C. It has been shown that any form of drying causes loss of coumarin from sweet clover (7,16) and, in this investigation, it was found that 20-40% was lost when sweet vernal was dried at 60°C for eight hours in a Unitherm oven whereas, except in one instance, no loss of related compounds occurred. It was also found that small amounts of coumarin were lost when fresh material was dried in a vacuum desiccator over sulphuric acid when suction was applied continuously for twelve hours.…”
Section: Methodsmentioning
confidence: 57%
“…In the past, workers have carried out analyses on fresh plant material, or on material dried either in a current of air at room temperature or by heating al: temperatures varying from 60-100°C. It has been shown that any form of drying causes loss of coumarin from sweet clover (7,16) and, in this investigation, it was found that 20-40% was lost when sweet vernal was dried at 60°C for eight hours in a Unitherm oven whereas, except in one instance, no loss of related compounds occurred. It was also found that small amounts of coumarin were lost when fresh material was dried in a vacuum desiccator over sulphuric acid when suction was applied continuously for twelve hours.…”
Section: Methodsmentioning
confidence: 57%
“…On the basis of the score limits listed in ta:ble 1 and the coumarin contents which have been found for the low-, bound-, and free-coumarin phenotypes of sweetclover (Haskins and Gorz ( 4), and unpublished results), the following score limits were set up for the three phenotypes: (1) low-not more than score 3 for either free or total coumarin, ( 2) bound-not more than score 2 for free coumarin and score 4 or more for total coumarin, and (3) free-score 3 or more for free coumarin and score 4 or more for total coumarin. It is recognized that the level of coumarin in second-year, field-grown plants at the time of flowering may be sufficiently high to necessitate a reduction in sample size in order to effect accurate differentiation of phenotypes with the standards used.…”
Section: Procedures and Resultsmentioning
confidence: 99%
“…ft are of extreme importance in achieving maximum efficiency in the development of strains of sweetdover low in coumarin content. In addition to being useful in the mass screening of large populations, rapid tests also are of value in genetic studies involving the two main pairs of alleles, Cujcu and Bjb, which appear to condition content and form of coumarin in the plant ( 2,4). If these genes are to be used as genetic markers, it is necessary that the qualitative test for coumarin permit the separate detection of both the free and bound forms, so that both allelic pairs can be identified.…”
Section: Deliable Qualitative Tests For Free and Bound Coumarinmentioning
confidence: 99%
“…It was found that their distribution resembled that found in sweet clover {Melilotus spp.) by Canadian workers (4). The greatest concentration occurs in leaf tissue, while stem and root tissues are low in these compounds.…”
Section: Sweet Vernal Grass {Anthoxanthum Ocluratum)mentioning
confidence: 94%